Host‐parasite relationship: occurrence and effect of Ceratothoa parallela (Otto, 1828) on Boops boops (L., 1758) in the Southern Tyrrhenian Sea. (19th June 2013) - Bottari, T.; Liguori, M.; Trilles, J. P.; Giordano, D.; Romeo, T.; Perdichizzi, F.; Rinelli, P.
Summary The host‐parasite relationship between bogue (Boops boops) and Cerathotoa parallela (Isopoda: Cymothoidae) was studied in the Southern Tyrrhenian Sea (overall prevalence of isopods in the area, age‐dependent and sex‐dependent prevalence). Yearly prevalence ranged from 1.0% in March to 10.7% in October, with a positive correlation between prevalence and mean sea surface temperatures (SST), highest values being related to the period of increasing SST. The first four age‐classes were parasitized, with prevalence decreasing according to the age of the host. The relationship between total length (TL) and total weight (TW) was examined in infested and non‐infested specimens of the same age whereby slight differences were detected, i.e. at a given length non‐infested specimens weighed more than infested fishes. The parasite occurred throughout the study area with wide fluctuations in prevalence, from 0 to 36.4%, the values being higher in the eastern part of the study area. C. parallela parasitize the bogue Boops boops in a manner that does not constitute a serious threat to the life of the host.